Strengthening Religious Character Values in Students in State MTs 1 Pesawaran - Yusuf, Ahmad Zakaria; Sada, Heru Juabdin; Baharudin, Baharudin (AR-RASYID : Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in strengthening the religious character values of students at MTs Negeri 1 Pesawaran through various strategies implemented in a planned manner. The study used a qualitative method with a case study approach through observation, interviews, and documentation of five key informants. The results showed that PAI teachers and guidance and counseling teachers implemented a number of strategies such as Al-Quran literacy before learning, a tahfiz program, the habit of congregational prayer, the implementation of 3S (smile, greet, say hello), the culture of shaking hands, and monitoring student behavior. These strategies have proven effective in shaping students' religious character, discipline, and responsibility. However, several obstacles were found, such as the school's location close to a busy center, low parental involvement, and negative peer influence. Overall, the role of teachers is very significant in creating a madrasah environment that is conducive to the formation of students' religious character.